2010
DOI: 10.1007/s11565-010-0105-1
|View full text |Cite
|
Sign up to set email alerts
|

Common fixed point theorems for families of compatible mappings in intuitionistic fuzzy metric spaces

Abstract: In this paper, we prove some common fixed point theorems for any even number of compatible mappings in complete intuitionistic fuzzy metric spaces. Our main results extend and generalize some known results in fuzzy metric spaces and intuitionistic fuzzy metric spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In 2004, Park [36] suggested the notion of intuitionistic fuzzy metric spaces (IFMS), which is a generalization of George and Veeramani's fuzzy metric space [15]. Many authors have recently proven fixed point theorems in IFMS ( [2,3,6,20,35,38,40,42,44]).…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, Park [36] suggested the notion of intuitionistic fuzzy metric spaces (IFMS), which is a generalization of George and Veeramani's fuzzy metric space [15]. Many authors have recently proven fixed point theorems in IFMS ( [2,3,6,20,35,38,40,42,44]).…”
Section: Introductionmentioning
confidence: 99%
“…Later Ç oker [6] introduced a topology on intuitionistic fuzzy sets. Park [21] introduced the notion of intuitionistic fuzzy metric spaces as a generalization to fuzzy metric spaces, which is a combination between intuitionistic fuzzy sets and the concept of a fuzzy metric space given by George and Veeramani [9], many authors established some results concerning fixed point in such spaces, see for example [2,5,12,14,19,29]. Meanwhile, jungck [16] defined the concept of compatible mappings, Jungck and Roadhes [17] generalized the last concept to the weakly compatible mappings, which is weaken than the compatible ones.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Park defined a Hausdorff topology on this kind of intuitionistic fuzzy metric spaces and showed that every metric induces an intuitionistic fuzzy metric. This result motivated many authors to study and investigate fixed point results in intuitionistic fuzzy metric (and normed) spaces (see, for examples, [1,3,7,9,20,22,31,34,35,40]). Since the intuitionistic fuzzy metric space has extra conditions, Saadati et al [38] modified the idea of intuitionistic fuzzy metric space and obtained various fixed point results in modified intuitionistic fuzzy metric spaces.…”
Section: Introductionmentioning
confidence: 99%